Discriminatory Treatment Against Minority Communities in Sharia Region: A Study of Parmalim Adherents in Aceh Singkil - Yasin, Taslim HM; Majid, Abd; Maizuddin, Maizuddin; Mardhatillah, Jundy (Religió Jurnal Studi Agama-agama, 2024)
This article describes the condition of Parmalim believers in Aceh Singkil who are marginalized and receive discriminatory treatment. This discriminatory treatment has left Parmalim believers in limbo when it comes to practicing their faith. The number of these believers in the area is decreasing day by day as more and more are converting to state-recognized religions. The research method used is the qualitative research method. The informants in this study consisted of key informants such as the village head, the secretariat of the Parmalim sect, the weekly ritual leader, and the Persantian board, as well as supporting informants, namely Parmalim believers who could provide additional information to enrich the data such as farmers, traders and people who are active in social activities in Parmalim. The results show that social activities and interactions between Parmalim believers and community members of other religions continue to run well. However, the phenomenon of discriminatory treatment against Parmalim believers is still ongoing. Proposals to repair places of worship to the Aceh Singkil Regional Government have never been fulfilled. In the field of education, there are no religious lessons or worship practices to strengthen the children of Parmalim followers. The children of Parmalim believers do not dare to reveal their beliefs, because the religious teachers at school only teach Islamic and Christian religious education.